The EZ-ALBI and PALBI scores contribute to the clinical application of ALBI in predicting postoperative recurrence of HCC - Tao Sun; Xiangkun Wang; Guangcan Zhu; Jinfu Zhang; Juan Huang; Renfeng Li; Xinguang Qiu (Scientific Reports)
Abstract This research intends to assess the variance between EZ-ALBI and PALBI in forecasting recurrence following the resection of hepatocellular carcinoma (HCC). A retrospective analysis was conducted using clinical data from 522 HCC patients across two medical institutions. The study analyzed albumin-bilirubin values (ALBI), along with the Easy albumin-bilirubin values (EZ-ALBI) and the Platelet-albumin-bilirubin values(PALBI), while assessing the clinical traits of patients across various grades. The analysis focused on the connections between ALBI, EZ-ALBI, and PALBI, as well as their variations in predicting the recurrence of HCC following surgical procedures. Notably, the clinical characteristics of patients exhibiting varying levels of PALBI differed from those categorized under ALBI and EZ-ALBI; however, the ALBI grade shared similar characteristics with the EZ-ALBI category. A strong correlation was found between ALBI and EZ-ALBI, with a coefficient of 0.862 (95% CI: 0.838–0.882, p < 0.01), whereas ALBI and PALBI yielded a coefficient of 0.760 (95% CI: 0.838–0.882, p < 0.01). The correlation coefficient between PALBI and EZ-ALBI was recorded at 0.571 (95% CI: 0.510–0.626, p < 0.01). There was a notable difference in survival outcomes among HCC patients classified with ALBI/EZ-ALBI/PALBI grade 1 compared to those with grade 2 or 3. Additionally, Cox regression analysis identified that maximum tumor diameter (MTD), microvascular invasion (MVI), pathological grade, as well as ALBI/EZ-ALBI/PALBI grades, among other factors, were tied to a decline in progression-free survival (PFS). The area under the curve (AUC) for the ALBI model at the 1, 2, and 3-year postoperative mark was 0.705, 0.652, and 0.694, respectively. In parallel, the AUC of the EZ-ALBI model during the same time intervals was 0.708, 0.659, and 0.694, respectively. For PALBI, the AUC values recorded at 1, 2, and 3 years following surgery were 0.748, 0.707, and 0.725, respectively. ALBI, EZ-ALBI, and PALBI served as predictive indicators for the recurrence of HCC in patients after surgery. Compared to ALBI, EZ-ALBI offers greater convenience in forecasting the prognosis of HCC patients, whereas PALBI demonstrates more accuracy than ALBI in predicting their prognosis.